Synthesis and Physicochemical Characterization of Undecylenic Acid Grafted to Hyaluronan for Encapsulation of Antioxidants and Chemical Crosslinking - Huerta-Ángeles, Gloria; Brandejsová, Martina; Kopecká, Kateřina; Ondreáš, František; Medek, Tomáš; Židek, Ondrej; Kulhánek, Jaromír; Vagnerová, Hana; Velebný, Vladimir (Polymers, 2019)
In this work, a new amphiphilic derivative made of 10-undecylenic acid grafted to hyaluronan was prepared by mixed anhydrides. The reaction conditions were optimized, and the effect of the molecular weight (Mw), reaction time, and the molar ratio of reagents was explored. Using this methodology, a degree of substitution up to 50% can be obtained. The viscosity of the conjugate can be controlled by varying the substitution degree. The physicochemical characterization of the modified hyaluronan was performed by infrared spectroscopy, Nuclear Magnetic Resonance, Size-Exclusion Chromatography combined with Multiangle Laser Light Scattering (SEC-MALLS), and rheology. The low proton motility and self-aggregation of the amphiphilic conjugate produced overestimation of the degree of substitution. Thus, a novel method using proton NMR was developed. Encapsulation of model hydrophobic guest molecules, coenzyme Q10, curcumin, and α-tocopherol into the micellar core was also investigated by solvent evaporation. HA-UDA amphiphiles were also shown to self-assemble into spherical nanostructures (about 300 nm) in water as established by dynamic light scattering. Furthermore, HA-UDA was crosslinked via radical polymerization mediated by ammonium persulphate (APS/TEMED). The cross-linking was also tested by photo-polymerization catalyzed by Irgacure 2959. The presence of the hydrophobic moiety decreases the swelling degree of the prepared hydrogels compared to methacrylated-HA. Here, we report a novel hybrid hyaluronan (HA) hydrogel system of physically encapsulated active compounds and chemical crosslinking for potential applications in drug delivery.
Keywords: crosslinking; hyaluronan; hydrogels; amphiphiles; esterification